INOVASI DIGITAL: PENERIMAAN DAN EFEKTIVITAS APLIKASI RUANG-GTK SEBAGAI WUJUD PEMERINTAH PROAKTIF DAN PERSONAL DI SEKTOR PENDIDIKAN KABUPATEN BANGKA BARAT - Yulianti; Arista, Sista (CORISINDO 2025, 2025)
This learning analyzes the acceptance and effectiveness of the Ruang-GTK application as a manifestation of a proactive and personalized government in the education sector of West Bangka Regency. Using the Technology Acceptance Model (TAM) framework, a survey of 250 elementary and junior high school teachers revealed that ease of use significantly influences perceived usefulness and user attitudes, with perceived usefulness being the dominant factor shaping positive attitudes. Although the application is considered easy to use, both its actual utilization and perceived benefits remain moderate. Furthermore, the presence of local digital platforms such as ASIK-GTK poses the risk of overlap, potentially hindering the optimal use of Ruang-GTK. These findings highlight the importance of system integration, improved digital literacy, and strengthened communication of service benefits to support the success of digital transformation toward more anticipatory and personalized public services.